POLYMORPHISMS OF PFCRT AND PFMDR-1 GENES AND CHLOROQUINE RESISTANCE OF P. FALCIPARUM IN WAD MEDANI (CENTRAL SUDAN) - Osman, Mohammed; El Tahir, Ahmed; Mergani, Adil; Al Balal, Mawia; Elamien, Mohammed; Elwali, Nasr Eldin. (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 1 (2009), 2009)
Introduction: Malaria parasite resistant to Chloroquine poses severe and increasing health problems in tropical countries. Monitoring the drug resistance by implementing the molecular markers may be essential to overcome the problem, therefore this study aims to assess the Chloroquine resistance of Plasmodium Falciparum parasite in central Sudan, using molecular markers. Methods:  One hundred and seventy six patients were confirmed P. falciparaum positive. Sixty-four were selected and only forty patients completed the follow-up. In vivo sensitivity assay was used accompanied with standard regimen of Chloroquine phosphate. DNA was extracted from blood on filter paper (day 0) and was used to amplify two genes P. Falciparum transporters gene Pfcrt and multi-drug resistant gene-1 Pfmdr-1. Results: Among forty patients, 54% responded to Chloroquine regimen with adequate clinical response (ACR), however, 46% showed treatment failure. All treatment failures were treated with Artemether or Quinine. The amplification of Pfcrt gene (n, 18) and Pfmdr 1 gene (n, 29), had shown that 72% of Pfcrt T76 were mutant allele, 22% were K76 wild-type, however, only 5% were mixed alleles T/K. while Pfmdr 1 gene (n, 29) revealed that 55% were wild genotype N 86, 38% were mutant Y 86, and 7% were mixed alleles Y/ N 86. Conclusion: The high frequency of the mutant Pfcrt 76T gene among P. Falciparum isolates was consistent with in vivo study supports the hypothesis that Pfcrt 76T gene could be used as predictive marker for Chloroquine susceptibility in epidemiological surveys.